Lithium Versus Other Mood Stabilizing Medications in a Longitudinal Study of Bipolar Youth RH = Lithium in Youth With Bipolar Disorder - Hafeman, Danella M. (J Am Acad Child Adolesc Psychiatry, 2019)
OBJECTIVE: Lithium (LI) is the mainstay for bipolar disorder (BD) treatment in adults, but evidence in youth is limited. We used data from the Course and Outcome of Bipolar Youth (COBY) study to assess whether LI vs. other mood stabilizing medication (OMS) was associated with improved outcomes, including mood symptoms and suicidality. METHOD: COBY is a naturalistic, longitudinal study of 413 youth, 7–17.11 years old at intake, with BD. At each visit, medication exposure, psychiatric symptoms, and psychosocial function over the preceding follow-up period were assessed using the Adolescent Longitudinal Interval Follow-Up Evaluation. Using mixed models, we determined whether participants taking LI vs. OMS (but not LI) differed regarding mood symptoms, suicidality, psychosocial function, hospitalization, aggression, and substance use. RESULTS: 340 participants contributed 2638 six-month follow-up periods (886 LI, 1752 OMS), over a mean follow-up of ten years. During LI (vs. OMS) follow-up periods, participants were older, less likely to have lifetime anxiety, and less likely to be on antidepressants (p-values<.005). After covariate adjustment, the LI group (vs. OMS) had half as many suicide attempts (p=.03), fewer depressive symptoms (p=.004), less psychosocial impairment (p=.003), and less aggression (p=.0004). Similar findings were observed in the subgroup of follow-up periods where participants were <18 years old. CONCLUSION: Findings are consistent with adult studies, showing that LI is associated with decreased suicidality, less depression, and better psychosocial functioning. Given the paucity of evidence regarding lithium in children and adolescents, these findings have important clinical implications for the pharmacological management of youth with BD.